Nitrogen incorporation in SnO2 thin films grown by chemical vapor deposition. Issue 6 (3rd February 2016) - Jiang, Jie; Lu, Yinmei; Kramm, Benedikt; Michel, Fabian; Reindl, Christian T.; Kracht, Max E.; Klar, Peter J.; Meyer, Bruno K.; Eickhoff, Martin
Abstract : The influence of nitrogen incorporation in high concentrations on the structural properties and morphology of SnO2 –x N x thin films grown by chemical vapor deposition is studied. A decrease in crystallite size and a lattice expansion in SnO2– x N x films with increasing x are found by X‐ray diffraction analysis and Raman spectroscopy. Substitutional nitrogen with a binding energy of 397.15 eV was detected by X‐ray photoelectron spectroscopy, attributed to the N 3 − ion in the SnN bond. The increase of the N atomic concentration x in SnO2 –x N x films from 0 to 7.9 at.% without phase separation with increasing NH3 flow rate during the deposition is accompanied by a decrease of O atomic concentration.